2011
DOI: 10.1021/jf203582k
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Thermal Degradation Kinetics of Chlorophyll Pigments and Ascorbic Acid from Ditax Nectar (Detarium senegalense J.F. Gmel)

Abstract: Detarium senegalense J.F. Gmel (ditax) is a forest tree found in Senegal the fruits of which are characterized by an attractive green flesh with a high amount in ascorbic acid. It is generally consumed as a nectar in Senegal. In this study, the main pigments of ditax pulp were identified and quantified by HPLC-DAD. Pheophytin a (128 mg/kg), which represents 58% of the total pigments, followed by hydroxypheophytin a' (33 mg/kg), chlorophyll b (24 mg/kg), and chlorophyll a (20 mg/kg) was the major pigment of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This is also reflected with the decrease of t 1/2 values with increasing temperature (Table ). Similar results were also determined by the authors studied anthocyanin, vitamin C and for other bioactive compounds' degradation kinetics for various food materials (Erenturk et al ., ; Verbeyst et al ., ; Ndiaye et al ., ). Figs and demonstrate the effect of temperature on the rate constants estimated by Arrhenius and Eyring–Polanyi equations to TPC and TA loss in arils.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is also reflected with the decrease of t 1/2 values with increasing temperature (Table ). Similar results were also determined by the authors studied anthocyanin, vitamin C and for other bioactive compounds' degradation kinetics for various food materials (Erenturk et al ., ; Verbeyst et al ., ; Ndiaye et al ., ). Figs and demonstrate the effect of temperature on the rate constants estimated by Arrhenius and Eyring–Polanyi equations to TPC and TA loss in arils.…”
Section: Resultsmentioning
confidence: 97%
“…Degradation rate constants were estimated using first-order kinetic model. Arrhenius model is the classic approach used for chemical reactions and often considered as reference, and Eyring-Polanyi model is based on the transition state theory (Cisse et al, 2009;Ndiaye et al, 2011). Drying equipment and pretreatment condition dependence of the degradation rate constants were expressed as activation energies, enthalpy and entropy according to Arrhenius (eqn 8) and Eyring (eqn 9) equations.…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have stated that thermal colour degradation also follows first order kinetics (Yoon et al, 2003;Sharma et al, 2008;Ndiaye et al, 2011). The important measure of quality for red pigments is the intensity of its red colour.…”
Section: Mathematical Modelling Of Colour Loss Kineticsmentioning
confidence: 99%
“…Reyes and Cisneros-Zevallos (2007) reported D values of 50-108 h at 80°C for the thermal stability of anthocyanins of purple and red-flesh potatoes in aqueous extracts, which would be much more stable. Ndiaye et al (2011) studied the thermal degradation kinetics of chlorophyll pigments and found values of 91-6 h at a temperature range of 60-95°C, which corresponds to a higher sensitivity to temperature than Table 3 indicates (lower value of z, or around 20°C only), so those pigments would be less stable than the ones used in this work at higher temperatures (from Table 1, D values at 60 and 95°C would be 42.7 and 8.7 h), and would be the same at 72°C.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%